Research on Evaluation Index and Application of Rockburst Risk in Deep Strip Mining - Bangyou Jiang; Hongguang Ji; Long Fu; Shitan Gu; Tong Zou; Jiaxin Lu (Shock and Vibration)
The practice shows that deep strip mining induces rockburst disaster easily. Accurately evaluating rockburst risk of the strip coal pillar is of great significance for ensuring the safety of deep strip mining. In this paper, the catastrophe mechanics model was used to analyze the abrupt instability condition of strip coal pillar. And the three indicators that are the medium stiffness ratio (k) of the elastic and plastic zone in the coal pillar, the plastic zone width ratio (aY), and the elastic deformation index (Uq) of core zone were put forward with considering the geometry size of coal pillar. Based on the 3202 panel of Gucheng Coal Mine, the evolution characteristics of rockburst risk of coal pillar under different mining widths and coal pillar widths were studied by numerical simulation. The evaluation result shows that the strip coal pillar of the 3202 panel is in danger of strong rockburst, which is more in line with the actual situation than the results of the traditional rockburst tendency identification test and comprehensive index method. These three indicators can be regarded as important indicators to evaluate the rockburst risk in the strip mining engineering field. Based on that, the design principle of strip mining in Gucheng Coal Mine was put forward, which is considered an important reference for similar cases.